Autoantibodies against interleukin 1α in rheumatoid arthritis: association with long term radiographic outcome. Issue 7 (1st July 2002) - Graudal, N A; Svenson, M; Tarp, U; Garred, P; Jurik, A-G; Bendtzen, K
Abstract : Objectives: To investigate the possible association of interleukin 1α autoantibodies (IL1α aAb) with the long term course of joint erosion in patients with rheumatoid arthritis (RA). Methods: Serum samples from 176 patients with RA included in a prospective study over 30 years were analysed for IL1α aAb by binding to human [ 125 I]IL1α. Erosions of 19 diarthrodial joints were radiographically scored by the Larsen method. Results: The relative risk (RR) of early IL1α aAb positive patients developing at least 30% of maximum radiographic joint destruction was significantly lower than for IL1α aAb negative patients, RR=0.29 (p=0.04). In rheumatoid factor positive patients RR was only 0.18 (p=0.02). Patients who seroconverted more than two years after the onset of RA showed the most aggressive development of joint erosion, with a relative risk of at least 40% of maximum radiographic joint destruction of 2.56 (p=0.048) Conclusions: The progression of radiographic joint destruction in patients with RA is associated with, and perhaps modified by, circulating IL1α aAb, suggesting that IL1α or IL1α aAb, or both, have a role in the erosive processes. IL1α aAb appear to be of prognostic significance in RA.